2019
DOI: 10.24246/agric.2019.v31.i1.p31-40
|View full text |Cite
|
Sign up to set email alerts
|

RESPONSE OF CELERY PLANT(Apium graviolens L.) TO THE REDUCTION OF INORGANIC FERTILIZER WITH DECANTER CAKE USAGE

Abstract: The purpose of this research was to find out the response of celery plants when inorganic fertilizers are reduced and substituted with oil palm decanter cake mill waste. This research was conducted at Farmer’s Field in Tangkit Baru Village, Sungai Gelam Sub-district, Muaro Jambi Regency, uses Randomized Block Design with one factor ie decanter cake and inorganic fertilizer (NPK) consists of 7 levels, namely: 100% NPK Fertilizer (as recommended 200 kg urea / ha, 150 kg / ha SP-36, 200 kg / ha KCl ), decanter ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
1
1
0
2
Order By: Relevance
“…Furthermore, the combination of DC and NPK gives the highest value of peanuts at DC dose of 26 tons ha-1 and NPK 50 percent of the recommended dose [16]. Similar results reported in celery plants showed DC dose 15 tons ha-1 combined with 50 percent of NPK showed the highest soybean yield in Ultisols [17] & [13].…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Furthermore, the combination of DC and NPK gives the highest value of peanuts at DC dose of 26 tons ha-1 and NPK 50 percent of the recommended dose [16]. Similar results reported in celery plants showed DC dose 15 tons ha-1 combined with 50 percent of NPK showed the highest soybean yield in Ultisols [17] & [13].…”
Section: Introductionsupporting
confidence: 55%
“…The organic waste of plant, supplies a good source of nutrients to enhance soil productivity [11] & [12]). Furthermore, [13] & [14] reported that the decanter cake (DC) has N content total of 4.22%, P2O5 4.272 mg 100g-1, K 2.044 mg 100g-1, organic C 27.43% and pH 7.32, and suitable for use as organic matter and a source of nutrients for Ultisols soil.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil penelitian Duaja, (2019) pada tanaman selederi menunjukkan DC 15 ton/ha yang dikombinasikan dengan pupuk kimia 50 persen memberikan hasil selederi tertinggi. Demikian juga pada tanaman kedelai di tanah gambut, hasil kedelai terbaik pada perlakuan DC 15 ton/ha yang dikombinasi dengan pupuk kimia 50 persen dari dosis anjuran (Duaja et al, 2019) . Demikian juga pada tanaman Kailan (Duaja et al, 2020), namun karena kalian ditanam di tanah bekas tambang hasil terbaik pada dosis DC 20 ton/ha kombinasi dengan pupuk kimia 50 persen.…”
Section: Abstrakunclassified
“…Bobot basah kalian tertinggi dicapai DC pada dosis 20 ton/ha yang dikombinasikan dengan pupuk kimia 50%, Selanjutnya pada tanaman selederi dosis DC dan pupuk NPK pada dosis 15 ton/ha + 50% NPK memberikan pertumbuhan dan hasil selederi tertinggi dan berpengaruh nyata terhadap jumlah daun, jumlah batang perumpun, berat basah dan berat kering akar tanaman seledri (Duaja, 2019). Selanjutnya pada penelitian Zainal et al, (2014), tanaman kedelai yang di berikan pupuk kandang ayam dosis 15 ton/ha, menghasilkan bobot polong isi per tanaman, bobot 100 biji dan hasil biji tertinggi.…”
Section: Abstrakunclassified